Effect of annealing time on morphological characteristics of Ba(Zr,Ti)O-3 thin films - Cavalcante, L. S.; Anicete-Santos, M.; Pontes, F. M.; Souza, I. A.; Santos, L. P. S.; Rosa, I. L. V.; Santos, M. R. M. C.; Santos-Junior, L. S.; Leite, E. R.; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Ba(Zr0.50Ti0.50)O-3 thin films were prepared by the polymeric precursor method using the annealing low temperature of 300 degrees C for 8, 16, 24, 48, 96 and 192 It in a furnace tube with oxygen atmosphere. The X-ray diffraction patterns revealed that the film annealed for 192 h presented some crystallographic planes (1 0 0), (1 1 0) and (2 0 0) in its crystalline lattice. Fourier transformed infrared presented the formation of metal-oxygen stretching at around 756 cm(-1). The atomic force microscopy analysis presented the growth of granules in the Ba(Zr0.50Ti0.50)O-3 films annealed from 8 to 96 h. The crystalline film annealed for 192 h already presents grains in its perovskite structure. It evidenced a reduction in the thickness of the thin films with the increase of the annealing time. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: annealing time; microstructure; thin films; BZT